Law, State and Telecommunications: from the outset to the new regulatory model (Law, State and Telecommunications Review, 2009)
This text introduces the Journal of Law, State, and Telecommunications, addressing, by way of an overview, its structure, contents and editorial policy. Besides that, this introduction defines the underpinnings of the journal’s regulatory approach such as concepts of regulation, regulatory law and telecommunications. It also addresses the historical and current stage of the Brazilian legal framework concerning telecommunications since the first republican constitution of 1891, with emphasis on the period between 1998 and 2008, the year of the tenth anniversary of the Brazilian National Agency of Telecommunications (ANATEL). Statutes, administrative regulation and judicial decisions of 2008 pertaining to telecommunications are referred to in detail, inaugurating the editorial proposal of registering the main political and juridical discussions about the Brazilian telecommunications sector that took place the year before the publication of the journal’s volume.